Atmospheric CO2 concentration effects on rice water use and biomass production - Kumar, Uttam; Quick, William Paul; Barrios, Marilou; Sta. Cruz, Pompe C.; Dingkuhn, Michael (Public Library of Science, 2017)
Numerous studies have addressed effects of rising atmospheric CO2 concentration on rice biomass production and yield but effects on crop water use are less well understood. Irrigated rice evapotranspiration (ET) is composed of floodwater evaporation and canopy transpiration. Crop coefficient Kc (ET over potential ET, or ETo) is crop specific according to FAO, but may decrease as CO2 concentration rises. A sunlit growth chamber experiment was conducted in the Philippines, exposing 1.44-m2 canopies of IR72 rice to four constant CO2 levels (195, 390, 780 and 1560 ppmv). Crop geometry and management emulated field conditions. In two wet (WS) and two dry (DS) seasons, final aboveground dry weight (agdw) was measured. At 390 ppmv [CO2] (current ambient level), agdw averaged 1744 g m-2, similar to field although solar radiation was only 61% of ambient. Reduction to 195 ppmv [CO2] reduced agdw to 56±5% (SE), increase to 780 ppmv increased agdw to 128±8%, and 1560 ppmv increased agdw to 142±5%. In 2013WS, crop ET was measured by weighing the water extracted daily from the chambers by the air conditioners controlling air humidity. Chamber ETo was calculated according to FAO and empirically corrected via observed pan evaporation in chamber vs. field. For 390 ppmv [CO2], Kc was about 1 during crop establishment but increased to about 3 at flowering. 195 ppmv CO2 reduced Kc, 780 ppmv increased it, but at 1560 ppmv it declined. Whole-season crop water use was 564 mm (195 ppmv), 719 mm (390 ppmv), 928 mm (780 ppmv) and 803 mm (1560 ppmv). With increasing [CO2], crop water use efficiency (WUE) gradually increased from 1.59 g kg-1 (195 ppmv) to 2.88 g kg-1 (1560 ppmv). Transpiration efficiency (TE) measured on flag leaves responded more strongly to [CO2] than WUE. Responses of some morphological traits are also reported. In conclusion, increased CO2 promotes biomass more than water use of irrigated rice, causing increased WUE, but it does not help saving water. Comparability with field conditions is discussed. The results will be used to train crop models